CYBERBULLYING PREVENTION INFORMATION SERVICE - Putri, Rasikha Aulia; Putri, Adhelia Syaharani; Oktariyani, Dhetalia; Ayunabila, Resty (Jurnal Kopendik, 2024)
Cyberbullying involves the use of digital technology to bully or harass someone. It commonly occurs on various online platforms, including chat rooms and gaming sites. Cyberbullying can be characterized by repetitive behavior and is often carried out with the deliberate intent of intimidating, belittling, or humiliating the victim. Unlike traditional bullying, cyberbullying leaves behind digital traces such as photos, images, or videos. Providing guidance and counseling services to students is a preventive measure that schools can take. The information service is one example of such a service. It facilitates understanding and prevention, thus helping students to comprehend themselves and stay up-to-date.